2017
DOI: 10.1002/2017gl075405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moon's Thermal State on the Impact Basin Ejecta Distribution

Abstract: We investigate how different temperature gradients of the Moon affect the ejection of lithic and molten materials for impact basin several hundred kilometers in diameter to quantify the thickness and melt content of ejecta blanket as a function of radial distance. We find, by means of numerical modeling, that the ejecta thickness and melt content, similar to the basin formation, is sensitive to the thermal properties of the target. For two similar impact scenarios, the ejecta thickness with radial distance is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…Also in large‐scale cratering processes, iSALE is capable of producing ejection data that agrees with observable constraints as shown for the Orientale basin on the Moon, where the simulated ejecta deposit (for different lunar thermal conditions) was compared with LOLA observations (Zhu et al. , ).…”
Section: Methodsmentioning
confidence: 65%
See 2 more Smart Citations
“…Also in large‐scale cratering processes, iSALE is capable of producing ejection data that agrees with observable constraints as shown for the Orientale basin on the Moon, where the simulated ejecta deposit (for different lunar thermal conditions) was compared with LOLA observations (Zhu et al. , ).…”
Section: Methodsmentioning
confidence: 65%
“…Detailed comparison between model outputs and NASA Ames experimental data for impacts into quartz sand from the 1970s have shown that the iSALE shock physics code can accurately simulate the ejection process (W€ unnemann et al 2016). Also in large-scale cratering processes, iSALE is capable of producing ejection data that agrees with observable constraints as shown for the Orientale basin on the Moon, where the simulated ejecta deposit (for different lunar thermal conditions) was compared with LOLA observations (Zhu et al 2015(Zhu et al , 2017.…”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…We assumed a vertical impact with a typical impact velocity of 15 km/s (Le Feuvre & Wieczorek, ) on a gabbroic target (Hurwitz & Kring, ; Potter et al, ). We tracked the ejecta trajectories during the impact cratering process and estimated the ejecta thickness at any given distance from the impact site (see Wünnemann et al, ; Zhu et al, , , ).…”
Section: Methodsmentioning
confidence: 99%
“…The three 360°image mosaics (left is north, clockwise) produced from the Pancam's left-eye images taken at the locations marked as black dots in Figure 2 labeled by S1, S2, and S3. tracked the ejecta trajectories during the impact cratering process and estimated the ejecta thickness at any given distance from the impact site (see Wünnemann et al, 2016;Zhu et al, 2015Zhu et al, , 2017Zhu et al, , 2019.…”
Section: Numerical Simulation Of Impact Ejectamentioning
confidence: 99%